QUALITY OF LIFE AND PHYSICAL ACTIVITY: A SELF PERCEPTION STUDY OF PEOPLE IN VALE DO SINOS, SOUTHERN BRAZIL. (Fiep Bulletin - online, 2013)
This descriptive study evaluated the association of quality of life and physical activity among adults aged 18 to 80 years in Vale dos Sinos, southern Brazil. A convenience sample of 1003 adults responded the short version of the IPAQ for physical activity and the WHOQOL-100 for quality of life. Data were analyzed using the ANOVA and the Tukey post hoc test (p=0.05). No significant differences were found between WHOQOL-100 domains and levels of physical activity. However, participants classified as low activity (LA) reported more fatigue and less energy than those classified as moderate (MA) and high activity (HA) (p=0.00) Similarly, those that had greater difficulties in performing activities of daily living were in the LA group, followed by those in the MA group (p=0.01). The analysis of the mobility facet showed that MA participants had higher scores than those in the LA and HA groups (p=0.01). Individuals in the MA group had the highest mean scores for positive feelings, followed by HA and LA ones. (p=0.01). Moreover, HA and MA individuals participated more or had more opportunities to participate in recreation and leisure activities than the LA group, respectively (p=0.00). The analysis of the environment domain showed that LA participants had the highest scores in the home environment facet, followed by MA and HA groups (p=0.05), differently from what was found for physical environment. In this case, HA participants perceived it in a healthier manner than the other adults (p=0.05). In the analysis of the four general questions in WHOQOL-100, the highest scores were found for MA participants, followed by HA and LA (p=0.05). MA adults had the highest mean scores, followed by HA and LA, which suggests that physical activity, when practiced at adequate intensities, brings benefits to health and, consequently, improves quality of life.
Keywords: Quality of life; Physical activity